Concurrent chemoradiotherapy by simultaneously integrated boost volumetric‐modulated arc therapy for nasopharyngeal carcinoma‐toxicity/quality of life and survival. Issue 5 (10th December 2018) - Fang, Fu‐Min; Huang, Tai‐Lin; Lin, Yun‐Hsuan; Chien, Chih‐Yen; Chuang, Hui‐Ching; Luo, Sheng‐Dean; Lin, Hsin‐Ching; Lin, Yu‐Tsai; Li, Shau‐Hsuan; Liao, Kuan‐Cho; Tsai, Wen‐Ling
Abstract: Background: To investigate the toxicity, changes of quality of life (QOL), and survival for patients with nasopharyngeal cancer (NPC) treated by concurrent chemoradiotherapy (CCRT) with simultaneously integrated boost volumetric‐modulated arc therapy (SIB‐VMAT). Methods: A total of 68 NPC patients treated by CCRT with SIB‐VMAT technique were collected. QOL was longitudinally assessed by the EORTC QLQ‐C30 and HN35 questionnaires at the 4 time points: baseline, 42.4 Gy (20 fractions), and 3, 12 months after CCRT. Results: The 4‐year locoregional relapse free, distant metastasis free, failure free, and overall survival rates were 97.0%, 86.4%, 82.0%, and 88.1%, respectively. The 4‐year cumulative incidence rate of late toxicities with grade 3 or more was 3.0%. One year after CCRT, most QOL scales, except some oral related symptoms, recovered to baseline level. Conclusion: CCRT with SIB‐VMAT produces excellent locoregional control, few severe late toxicity, and good general health status for NPC patients.